The "terrorist" in criminal law: for a intercultural criminal politics (2010)
In the modern history of Western Civilisation, the term “terrorism” has been used without the appropriate care, making it a very vague and diffuse one. On the other hand, a more precise concept –which is similar to the partisan described by Carl Schmitt-